Multi-walled carbon nanotubes produced after forest fires improve germination and development of Eysenhardtia polystachya - Gladys Juárez-Cisneros; Mariela Gómez-Romero; Homero Reyes de la Cruz; Jesús Campos-García; Javier Villegas (PeerJ, 2020)
Background Multi-walled carbon nanotubes (MWCNTs) are nanoparticles with countless applications. MWCNTs are typically of synthetic origin. However, recently, the formation of MWCNTs in nature after forest fires has been documented. Previous reports have demonstrated the positive effects of synthetic MWCNTs on the germination and development of species of agronomic interest; nevertheless, there is practically no information on how synthetic or natural MWCNTs affect forest plant development. In this report, based on insights from dose-response assays, we elucidate the comparative effects of synthetic MWCNTs, amorphous carbon, and natural MWCNTs obtained after a forest fire on Eysenhardtia polystachya plant. Methods E. polystachya seeds were sown in peat moss-agrolite substrate and conserved in a shade house. Germination was recorded daily up to 17 days after sowing, and plant development (manifested in shoot and root length, stem diameter, foliar area, and root architecture parameters) was recorded 60 days after sowing. Results The treatments with natural MWCNTs accelerated the emergence and improved the germination of this plant, thus while untreated seeds achieve 100% of germination within 16th day, seeds supplemented with natural MWCNTs at doses of 20 µg/mL achieve the above percentage within the 4th day. Natural MWCNTs also promoted fresh and dry biomass in all applied treatments, specially at doses of 40 µg/mL where natural MWCNTs significantly promoted leaf number, root growth, and the dry and fresh weights of shoots and roots of seedlings. Seeds supplemented with doses between 20 and 40 µg/mL of amorphous carbon achieving 100% of germination within the 6th day; however, seeds supplemented either with doses of 60 µg/mL of the above carbon or with synthetic MWCNTs at all the tested concentrations could achieve at most 80 % and 70% of germination respectively within the 17 days. Finally, neither treatments added with amorphous carbon nor those added with synthetic MWCNTs, showed significant increases in the fresh and dry biomass of the tested plant. Likewise, the survival of seedlings was reduced between 10 and 20 % with 40 and 60 µg/mL of amorphous carbon, and with synthetic MWCNTs in all the doses applied was reduced at 30% of survival plants. Conclusions These findings indicate that MWCNTs produced by wildfire act as plant growth promoters, contributing to the germination and development of adapted to fire-prone conditions species such as E. polystachya.